2016
DOI: 10.1155/2016/9101762
|View full text |Cite
|
Sign up to set email alerts
|

MIF Promotes Classical Activation and Conversion of Inflammatory Ly6ChighMonocytes into TipDCs during Murine Toxoplasmosis

Abstract: Macrophage migration inhibitory factor (MIF) mediates immunity against Toxoplasma gondii infection by inducing inflammatory cytokines required to control the parasite replication. However, the role of this inflammatory mediator in the cell-mediated immune response against this infection is still poorly understood. Here, we used T. gondii-infected WT and Mif −/− mice to analyze the role of MIF in the maturation of CD11b+ and CD8α + dendritic cells (DCs). We found that MIF promotes maturation of CD11b+ but not C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…Nevertheless, additional studies are needed to more precisely clarify the roles of MIF and D-DT in MS, especially with respect to the mechanistic role of their common receptor CD74 and that of the noncognate chemokine receptors CXCR2 and CXCR4 (9). Furthermore, it would be interesting to evaluate whether increased MIF and D-DT levels in MS might promote the activation of Ly6C hi inflammatory monocytes similar to their effects described in parasite infections (55).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, additional studies are needed to more precisely clarify the roles of MIF and D-DT in MS, especially with respect to the mechanistic role of their common receptor CD74 and that of the noncognate chemokine receptors CXCR2 and CXCR4 (9). Furthermore, it would be interesting to evaluate whether increased MIF and D-DT levels in MS might promote the activation of Ly6C hi inflammatory monocytes similar to their effects described in parasite infections (55).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been proposed that DC orchestrate the autoimmune response in T1DM via TLR-2 and TLR-4 [ 58 ]. Previous studies by us and others have shown that Mif induces the expression of costimulatory molecules on M φ and DC in some pathological infections [ 59 61 ]. Here, we identified the expression of costimulatory molecules and TLR-2 and TLR-4 on M φ and DC, as well as the ability of M φ to activate T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the previous studies showed that MIF reduced the Toxoplasma infection in in vivo and in vitro experimental models. One group demonstrated that MIF promotes the classical activation of monocytes, promoting resistance to T. gondii infection in MIF −/− mice treated with recombinant MIF (Ruiz-Rosado et al., 2016). Another study using T. gondii -infected MIF −/− mice showed reduced lethality, as well as ileum inflammation and tissue damage, despite increased parasite intestinal load in relation to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%